The Organizational Context of Research-Minded Practitioners: Challenges and Opportunities. (July 2015) - McBeath, Bowen; Austin, Michael J.
If some practitioners are more research minded than others, then promising approaches for bridging the research to practice gap may be developed by describing research-minded practitioners and examining how to locate and support them. This article follows this basic logic in providing an overview of organizational development and practitioner support models for increasing knowledge use in human service organizations. The article begins with a conceptual profile of research-minded practitioners—individuals with an affinity for empirical inquiry, critical thinking, and reflection allied with a commitment to data-driven organizational improvement—and the organizational settings needed to host research-minded practice. This is followed by a description of the challenges involved in promoting practitioner involvement in using, translating, and doing research and strategies to address these challenges. We conclude with implications for supporting research-minded practitioners and aligning their efforts with organizational improvement processes. The goal of the analysis is to identify the organizational contexts in which research-minded practitioners can thrive as well as new directions for practice research.